Soil microbial communities are more disrupted by extreme drought than by gradual climate shifts under different land-use intensities - Philipp, Lena; Blagodatskaya, Evgenia; Tarkka, Mika; Reitz, Thomas (Frontiers in Microbiology, 2025)
IntroductionExtreme events like droughts are expected to increase in frequency due to climate change and will affect ecosystems and their associated key functional components particularly soil microbial communities. Studies simultaneously addressing a range of climate stressors, such as extreme drought events and gradual long-term shifts in precipitation and temperature on soil microbial diversity, community composition and function in agricultural systems are limited.MethodsHere, we present a data set from a field site in Central Germany comprising two spring growing seasons, one with normal precipitation amount, the other experiencing an extreme drought. Further, the experiment included a climate treatment simulating climate change induced gradual shifts in precipitation and temperature in croplands and grasslands under varying management intensities.Results and discussionOur findings demonstrate that the extreme drought had a stronger effect on microbial biomass, functions and community composition than the mild experimental climate treatment mediated by soil moisture differences. The fungal communities were more responsive to the drought than the bacterial community, particularly in croplands, where we observed higher C-cycling enzymatic activities under drought. In contrast, microbial functions in grasslands remained largely unchanged in grasslands under drought, implying lower sensitivity to drought in grassland than cropland systems. However, intensively managed grasslands appeared less stable in community composition and function than extensively managed grasslands, which was also observed in constructed co-occurrence networks. Overall, our results suggest that intensively managed systems are more vulnerable to extreme drought conditions with an increase of fungi with pathogenic potential which may further destabilize soil microbial communities in the future These findings underscore the need to consider multiple stressors such as extreme events and land-use intensity in order to understand the soil microbial response to global change.